New Health Technologies: A UK Perspective; Comment on "Providing Value to New Health Technology: The Early Contribution of Entrepreneurs, Investors, and Regulatory Agencies" - Nassim Parvizi; Sahar Parvizi (Kerman University of Medical Sciences, 2017)
New health technologies require development and evaluation ahead of being incorporated into the patient care pathway. In light of the recent publication by Lehoux et al who discuss the role of entrepreneurs, investors and regulators in providing value to new health technologies, we summarise the processes involved in making new health technologies available for use in the United Kingdom.